ANALYSIS OF STUDENT RESPONSE TO TEACHER WRITTEN CORRECTIVE FEEDBACK IN WRITING A DESCRIPTIVE TEXT - Mahmud Layan Hutasuhut; Emalia Kurnia Nanda (Universitas Negeri Medan, 2022)
Abstract This research describes students’ responses to teacher written corrective feedback in their descriptive texts. It also discovers types of written corrective feedback used by the teacher. The research employed descriptive qualitative. The subjects of the study consisted of 16 seventh year students of SMP Negeri 1 Tanjung Beringin and an English teacher. Open-ended interview and documentation review were used as the research instruments to collect the data. Results of the study revealed that (1) the majority of the students showed positive responses to teacher’s written corrective feedback, as the following: (a) They said that teacher written corrective feedback was useful, (b) they felt pleased when their descriptive texts were provided with written corrective feedback, (c) teacher written corrective feedback made them feel motivated in writing, (d) they hoped the teacher always provided written corrective feedback to improve their writing errors, and (e) direct written corrective feedback served as the most preferred teacher feedback, and that (2) of the three types of written corrective feedback (metalinguistic, direct and indirect), the teacher only used direct and indirect written corrective feedback in the students’ descriptive texts.) Keywords: Student response; teacher written corrective feedback; assessment; descriptive text